The Effects of Internationalization on CEO Compensation - Lars Oxelheim; Trond Randøy (The Research Institute of Industrial Economics (IUI), 2004)
This study examines the relation between the internationalization of firms and CEO compensation. Starting from a sample of Norwegian and Swedish listed firms we analyze the effects of internationalization as manifest in the capital market (international cross-listing), the market for corporate control (foreign board membership), and the product and service market (export and foreign sales). We conclude that all three markets contribute positively to the compensation level of CEOs. We argue that part of the higher CEO compensation in internationally oriented firms - as compared to less internationalized firms within the same country - reflects a risk premium for reduction in job security.
Keywords: G34; K12; M10; M12; 330; CEO Compensation; Internationalization; Corporate Governance; CEO Tenure; Cross-Listing; Foreign Board Membership; Führungskräfte; Vergütungssystem; Multinationales Unternehmen; Norwegen; Schweden